Propose a Polynomial Time Algorithm for Total Completion Time Objective - Ozturkoglu, Yucel; Ozturkoglu, Omer (International journal of mathematical, engineering and management sciences, 2021)
In this study, we integrate deteriorate jobs with repair&maintenance activity on a single machine scheduling subject to total completion time. This work has more than one motivation. First, jobs are assigned to machines in an automated production line. Later, to schedule the maintenance activities, if needed, to prevent machinery from breaking down later. There are some important mathematical models to solve this combination. However, due to the complexity of the problem which is Np-hard, a polynomial algorithm should be needed for solving large problems. Therefore, this article introduces several polnomial algorithms to determine the order of things best. With using these algorithms, it will be possible to determine where to assign to the schedule, taking into account the number of maintenance activities required and their optimum total completion time.